The Relationship Between Teaching Efficacy and Teachers' Perceptions of Student Engagement in Online Learning During the Covid-19 Pandemic - Egi Yolanda Putri; Narulita Septa Aminingtyas; Mia Dwi Pratiwi (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the relationship between teaching efficacy and teachers' perceptions of student engagement in online learning during the Covid-19 pandemic. This research used quantitative methods. Respondents in this study amounted to 202 people obtained using an online questionnaire on teachers who conducted online learning with non-probability sampling techniques. Tools to measure teaching efficacy using Teacher Efficacy Scale (TES). The tool to measure teachers' perception of student engagement used Student Engagement Instrument (SEI). The data in this study were analyzed using Pearson correlation technique. The results in this study showed that there was a positive relationship among teaching efficacy and teachers' perceptions of student engagement (r = 0.552; p < 0.05).